2011
DOI: 10.1093/ndt/gfr312
|View full text |Cite
|
Sign up to set email alerts
|

Additional role of urine output criterion in defining acute kidney injury

Abstract: Although some AKI cases were not identified by the UOCr alone, the UOCr has an additional role in AKI staging, regardless of diuretic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…11,12 Han and his colleagues reported that the percentage of AKI diagnosed by urine output criteria alone occurred between 2.9% and 25.7%, and their research reached 7.9%. 13,22 AKI has been well described in geriatric population, and an increased incidence of AKI becomes higher than previous studies (2-25%). 24 The proportion of AKI in these patients is 33.6% due to the use of angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) prior to surgical intervention.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…11,12 Han and his colleagues reported that the percentage of AKI diagnosed by urine output criteria alone occurred between 2.9% and 25.7%, and their research reached 7.9%. 13,22 AKI has been well described in geriatric population, and an increased incidence of AKI becomes higher than previous studies (2-25%). 24 The proportion of AKI in these patients is 33.6% due to the use of angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) prior to surgical intervention.…”
Section: Discussionmentioning
confidence: 78%
“…19,20 Following the insufficiency of serum creatinine responsible for AKI, the next major quantum of deficiency in the field arose from the understanding that the limitations of the urine output criteria and inappropriately identifying prognostic factors of mortality in patients with AKI. 21,22 Because the factors including volume status and nutrition status that affect creatinine, serum creatinine was found to be subnormal standard biomarker for AKI. One report describe that plasma neutrophil gelatinase-associated lipocalin (NGAL) and serum cystatin C were better prognostic factors of AKI following cardiac surgery compared to serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only effect this manipulation carried on our results was to potentially underestimate the change in eCCl from baseline • The worse part (either eCCl or FO) was used to stage AKI as in some cases Fluid overload was not known and only eCCl was used to stage AKI according to KDIGO guidelines. (few studies found no significant differences in RAI prediction of AKI when the outcome was based on creatinine or urine output 20 • We did not test the RAI on ICU admission days other than Day 0 or to predict AKI persistence after ICU Day 3 and acknowledge that the RAI performance may be better or worse than the clinical context we tested.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that UO is a sensitive and early marker for AKI in patients in the ICU and has additional roles in AKI staging (19,20). There is still controversy, however, about the application of UO criteria, especially in non-ICU patients.…”
Section: Discussionmentioning
confidence: 99%